Assessing the magnitude of burnout among emergency nurses in Portugal - Fernandes, Júlio Belo; Antunes, Ricardo; Ivanel, Maria; Lucas, Mariana; Oliveira, Ricardo; Bico, Wilson; Simões, Aida; Vareta, Diana; Bernardes, Catarina; Vaz, Célia; Hall, Steven; Fernandes, Sónia; et al. (Frontiers in Public Health, 2025)
BackgroundBurnout is a health condition associated with chronic work-related stress. Nurses working in hospital emergency rooms are particularly susceptible to experiencing burnout. It is crucial to understand the phenomena of burnout among emergency room nurses, particularly in light of the COVID-19 pandemic that healthcare professionals have confronted. This study aims to evaluate burnout among nurses working in emergency rooms while examining the relationship between burnout and sociodemographic and occupational variables.MethodsThis descriptive, observational, and cross-sectional study utilized a web-based survey administered to 112 nurses from eight hospital emergency rooms in the Lisbon metropolitan area between November 2022 and February 2023. Burnout was measured using the Portuguese version of the Maslach Burnout Inventory (MBI), which assessed three subscales: Emotional Exhaustion (EE), Depersonalization (DP), and Personal Accomplishment (PA). The relationship between burnout and sociodemographic and professional characteristics of nurses in emergency rooms was analyzed using Chi-square tests and one-way ANOVA.ResultsThe prevalence of burnout was 56.6%, with 27.4% experiencing severe burnout. The three subscales of the MBI showed high prevalence rates: 49.1% for EE, 44.6% for DP, and 38.4% for low PA. Severe burnout and high EE were associated with younger age, being single, not having children, having less professional experience, less graduate training, and having more precarious employment contracts.ConclusionsThree years after the onset of the COVID-19 pandemic, the results highlight the ongoing critical situation arising from the cumulative effects of the crisis on the Portuguese healthcare system, leading to high rates of burnout and EE among emergency room nurses.